Nutritional and metabolic evaluation of feeding lambs with growing levels Of protein amino acids - Araujo, C. M.; Junior, G. L. Macedo; Oliveira, K. A. [UNESP]; Silva, A. L.; Santos, M. T. S. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The objective was to evaluate the inclusion of protected lysine and methionine levels on the diet, over the nutritional parameters and energetic and hepatic metabolites of growing lambs. Five lambs 1/2 blood Dorper x Santa Ines, with approximately eight months of age and average weight of 50kg, were distributed in a 5x5 latin square scheme (five treatments and five replicates). The treatments consisted of the inclusion of different levels of lysine and methionine protected from ruminal degradation (MicroPEARLS LM (R)) in the diet, being: 0g, 8g, 16g, 24g and 32g. The diet was composed of corn silage and concentrated 30V:70C in the ratio. A digestibility assay was performed to determine dry matter intake and digestibility (DMI/DDMI), nitrogen balance and blood metabolites. The DMI (kg/day) in relation to the metabolic weight had a positive linear equation, being higher in treatment 32g, as well as the ingested nitrogen and nitrogen balance, being positive in all treatments. There was no difference (P>0.05) for the digestibility of DM, energetic and hepatic metabolism. Lysine and methionine protected from ruminal degradation can be included in the diet of growing lambs up to 32g without causing negative effects on DM digestibility and metabolism.
Keywords: dry matter intake; digestibility; energy; hepatic; sheep